Kenneth Burke - American Writers 75 : University of Minnesota Pamphlets on American Writers - Brown, Merle Elliott, 1925- (Book collections on Project MUSE., 1969)
Kenneth Burke - American Writers 75 was first published in 1989. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions.